IDENTIFICATION OF THE DISTRIBUTION OF BLANK SPOT AREAS OF THE GSM NETWORK ON SEVERAL ROAD SECTIONS OF RASAU JAYA DISTRICT USING THE DRIVE TEST METHOD - Rizki, Muhammad Nur; Marpaung, Jannus; Imansyah, Fitri (Faculty of Engineering, Universitas Tanjungpura, 2024)
This research investigates blank spot areas on the GSM network in Rasau Jaya District with an emphasis on several roads. The drive test method and G-Nettrack application are used to identify and measure signal quality, especially RSRP (Reference Signal Received Power), from three main providers: Telkomsel, H3I, and Indosat. The research results reveal significant variations in RSRP values in blank spot areas on primary and secondary roads. On primary road Telkomsel providers with signal categories are: Very Good 77, Good 237, Not Good 227, Very Bad 465. Indosat Ooredo Primary Road, Very Good 118, Good 462, Not Good 356, Very Bad 200, H3I Primary Road , Very Good 118, Good 230, Not Good 409, Very Bad 175. Then data Telkomsel Secondary Road Very Good 60, Good 287, Not Good 75, Very Bad 1232. Indosat Ooredo Secondary Road, Very Good 122, Good 102 No Good 158, Very Bad 1372, H3I Secondary Road, Very Good 117, Good 135, Not Good 145, Very Bad 1362. Data analysis confirms that the further the measurement distance from the Base Transceiver Station (BTS), the signal quality tends to decrease, especially in the very bad category. Identification of the distribution of blank spot areas also provides insight into locations that require signal improvement, providing a basis for improvement steps in developing the GSM network in the region.